Reinforced Concrete Bridge Deck Model Considering Delayed Exposure to Chlorides - Konečný, Petr; Lehner, Petr; Pustka, David (Periodica Polytechnica Civil Engineering, 2019)
The paper is focused on the model of the effect of delayed chloride exposure on the chloride induced corrosion initiation on ideal reinforced concrete bridge. The Finite Element-based numerical model is applied. The effect of concrete quality is expressed in the form of time dependent diffusion coefficient in order to evaluate the effect of concrete type as well as the effect of aging. The influence of extended chloride exposure on the corrosion initiation is introduced.